Diptera Collectionis P. Gabriel Strobl - IX (Supplementa ad Partes I et V). - Morge, Günter (Contributions to Entomology = Beiträge zur Entomologie, 1976)
Additional information is given to parts I and V of the list of Strobl's collection of Dipterta.